2009
DOI: 10.1140/epjc/s10052-009-1071-6
|View full text |Cite
|
Sign up to set email alerts
|

Probing unparticle theory via lepton-flavor violating process J/ψ→ll′ at BESIII

Abstract: The lepton flavor violating process J/ψ → ll ′ (l = l ′ ) serves as an ideal place to probe the unparticle theory. Such process can only occur at loop level in the Standard model (SM), so that should be very suppressed, by contrast in unparticle scenario, it happens at tree level and its contribution may be sizable for practical measurement. Moreover, the BESIII will offer the largest database on J/ψ which makes more accurate measurements possible. Furthermore, for such purely leptonic decays background is rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Here ∆M ν is the difference between the masses of neutrinos of different flavor and M W is the mass of the charged weak vector boson. Hence, CLFV offers an opportunity to probe signature of new physics [42][43][44][45][46]. The CLFV charmonium decays J/ψ → ll ′ (l and l ′ = τ, µ, e, l = l ′ ) are predicted by various theoretical models that allow tree-level FCNC, including, e.g., unparticle theory [46,47], R-parity violating and large tanβ SUSY scenarios, leptoquarks, and other models inspired by the idea of grand unification [44,45].…”
Section: Search For the Invisible Decays Of Quarkoniummentioning
confidence: 99%
“…Here ∆M ν is the difference between the masses of neutrinos of different flavor and M W is the mass of the charged weak vector boson. Hence, CLFV offers an opportunity to probe signature of new physics [42][43][44][45][46]. The CLFV charmonium decays J/ψ → ll ′ (l and l ′ = τ, µ, e, l = l ′ ) are predicted by various theoretical models that allow tree-level FCNC, including, e.g., unparticle theory [46,47], R-parity violating and large tanβ SUSY scenarios, leptoquarks, and other models inspired by the idea of grand unification [44,45].…”
Section: Search For the Invisible Decays Of Quarkoniummentioning
confidence: 99%
“…At first sight, the unparticle scenario might provide a larger contribution to the decay mode because no heavy weak scale M W exists at its propagator. However, the data of D 0 − D0 mixing, [13] neutrino experiment [24] and lepton flavor violation [25] rigorously constrain the effective couplings of the unparticle and the SM particles, thus one cannot freely adjust anything at all. The resultant contribution of the unparticle to the decay width is many orders of magnitude smaller than that of the SM.…”
Section: -3mentioning
confidence: 99%
“…Nevertheless, the branching ratios of the LFV decays can be enhanced in various extensions of the SM, such as the grand unified models [10][11][12], the supersymmetric models with and without R-parity [13,14], the left-right symmetry models [15][16][17] and so on. The LFV decays of the neutral vector mesons have been studied in several new physics scenarios [9,[18][19][20][21][22][23] and in a model-independent way [24][25][26][27][28][29]. It has been shown that BR(V → l 1 l2 ) can be significantly enhanced close to the current or future experimental sensitivities.…”
Section: Introductionmentioning
confidence: 99%